2023
DOI: 10.1021/acsnano.2c11071
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugation-Assisted Growth of Single-Crystalline Grains in Microcapsules

Abstract: Colloidal crystals have been tailored in a format of microspheres to use them as a building block to construct macroscopic photonic surfaces. However, the polycrystalline grains grown from the spherical surface usually exhibit low reflectivity. Although single-crystalline microspheres have been produced, it is difficult to control the crystal orientation. Here, we design spherical microcapsules with density anisotropy that contain single-crystalline grains along the heavy side. The microcapsules spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Monodisperse colloids spontaneously produce crystalline lattices, which have been used as photonic materials with bandgap properties. The colloidal crystals have been tailored in a format of spherical microparticles by employing emulsion droplets as a confining geometry. , The photonic supraballs have served as structural colorants, , colorimetric microsensors, display pixels, and optically encoded microcarriers, which are difficult to apply with a bulk film format. In addition, the emulsion droplets provide a tool to study the crystallization behavior of colloids under spherical confinement. It has been revealed that single-crystalline face-centered cubic (fcc) structures with surface termination to fit into a sphere are energetically more favorable than onion-like or polycrystalline structures. , The photonic supraballs composed of single-crystalline colloidal arrays are optically anisotropic as the crystal planes responsible for diffraction vary depending on the orientation of supraballs. , Therefore, the single supraballs show various reflection colors from their entire projection as they rotate.…”
mentioning
confidence: 99%
“…Monodisperse colloids spontaneously produce crystalline lattices, which have been used as photonic materials with bandgap properties. The colloidal crystals have been tailored in a format of spherical microparticles by employing emulsion droplets as a confining geometry. , The photonic supraballs have served as structural colorants, , colorimetric microsensors, display pixels, and optically encoded microcarriers, which are difficult to apply with a bulk film format. In addition, the emulsion droplets provide a tool to study the crystallization behavior of colloids under spherical confinement. It has been revealed that single-crystalline face-centered cubic (fcc) structures with surface termination to fit into a sphere are energetically more favorable than onion-like or polycrystalline structures. , The photonic supraballs composed of single-crystalline colloidal arrays are optically anisotropic as the crystal planes responsible for diffraction vary depending on the orientation of supraballs. , Therefore, the single supraballs show various reflection colors from their entire projection as they rotate.…”
mentioning
confidence: 99%
“…2c). This phenomenon can be attributed to a diffusive mass flow resulting from a concentration gradient induced by the UV intensity gradient, which serves as the primary driving force for molecules within our aligned hydrogel scaffold 31 . This gradient, absent in thermo-curing hydrogels, serves as the primary force propelling molecules within our aligned hydrogel scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32] Among these soft matters, polymer brushes offer greater advantages in terms of devices as they allow control of nanostructure arrangements on solid substrates by nanoscale conformation changes without macroscale size changes of the matrix. [33][34][35][36][37][38] These characteristics, as well as the inherent anisotropy of polymer brushes, are expected to be more suitable to control the orientation of anisotropic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%